PERSEPSI MASYARAKAT TERHADAP “LABEL” WILAYAH BASIS TERORIS (STUDI KASUS PERSEPSI MASYARAKAT SOLA RAYA) - Reni Windiani (JURNAL LITBANG PROVINSI JAWA TENGAH, 2016)
Two important concepts in labeling theory are the primary deviance and the secondary deviance. Primary deviance is the initial act of deviance. Meanwhile, secondary deviance is related with psychological reorganization of one’s experience, as a result from being publicly labeled as deviant. Once a label attached to a person, it is very difficult for someone to further break away from that label, and will then identify itself with the label that has been given by community. Central Java is one area in which terrorists were found. Therefore, Central Java is labeled as a terrorist base area. By using quantitative research method, this study aims to analyze public perception in “Solo Raya”, regarding its label as a terrorist base area. This research was conducted in Surakarta, Sukoharjo, and Sragen. The result of this research shows that labelling terrorist base area has slight influence to the behavior of the people in the three areas. This is because the respondents understand the definition of terrorism; which connotes negative, and disturbing public. All of the respondents have the same perception, which is that terrorism is a crime that disrupt people’s lives. Thus, respondents do not have willingness to behave like terrorists, though they were disappointed by the government.